The Relationship Between Level of Transforming Growth Factor - Î² with Pulmonary Fibrosis in Post Pulmonary Tuberculosis in Medan - Christine, Tamara; Tarigan, Amira Permatasari; Nainggolan, Nuryunita; Zaluchu, Fotarisman (Jurnal Respirologi Indonesia, 2020)
Background: Untreated or undertreated, pulmonary tuberculosis could cause severe complications until death. After treatment, residual lesions might occur. The presence of residual lesions is varied, including: fibrosis, cavity, bronchiectasis and calcification. Transforming growth factor-Î² (TGF-Î²) is a cytokine associated with lung inflammation, which plays a role in lung fibrosis. However, only a few studies have assessed the serum level of TGF-Î² in post-treatment tuberculosis patients. The main objective of this study was to determine the relationship between TGF-Î² levels and pulmonary fibrosis in patients with pulmonary tuberculosis. Methods: Among 51 patients that had undergone anti-tuberculosis treatment were observed, consisting of 31 men, 20 women. Of all patients, there were 26 people with a smoking history, including 25 men and 1 woman. All patients had been recovered, confirmed by clinical state, laboratory and radiology examination. The ELISA test was performed to measure TGF-Î² level, while chest X-ray was used to evaluate for the occurence of pulmonary fibrosis. Results: The mean level of TGF-Î² in patients with lesion (+) was 7628.02 pg/mL (SD: Â±4928.38) while the mean level of TGF-Î² in patients with lesion (-) was 2315.11 pg/mL (SD: Â±505.83). Statistical test showed a significant relationship between TGF-Î² level and fibrosis lesion (P